Escherichia coli Contamination on Cutlery (Glass) in Malioboro Tourism Area Yogyakarta - Dyah Suryani; Wibowo Wibowo; Iga Umari (Alliance oh Health Activists (AloHA), 2019)
Angkringan is one of the favorite food stalls in the Malioboro area of Yogyakarta. Poor hygiene in food can cause food contamination. One of them is contamination caused by unclean cutlery and resulting in disease due to bacterial contamination. The purpose of this study was to determine the factors associated with Escherichia coli contamination on cutlery (glass) at the angkringan Malioboro Tourism area, Yogyakarta. This study used a cross sectional study. The research subjects were angkringan which numbered 40 angkringan, the object of the research was 40 sample of cutlery and clean water. The research instrument is a questionnaire and checklist. Data analysis with univariate and bivariate analysis. The results of bivariate analysis revealed the positive association between personal hygiene and sanitation facilities and E. coli contamination (p value = 0.046, p value = 0.037, respectively). Additionally, it also found without association between knowledge, attitude, management of cutlery and the presence of E. coli in clean water with contamination of E. coli. Personal hygiene and sanitation are the determinants of E. coli contamination on cutlery (glass) in Malioboro Tourism Area in Yogyakarta. The management and monitoring regarding food assessment is needed to prevent the communicable disease caused E. coli. Keywords: E. coli, Cutlery, Hygiene sanitation, Angkringan